Traçados de caldeiraria no desenvolvimento da geometria no ensino médio - Dias, Rodrigo Domingos (Universidade Federal de São Carlos, 2014)
A course of Professional Qualification in Boiler Tracing aims to develop the capacities to calculate, chart, plan parts, prepare technical design, modeling sets and subsets. However the aim of this work is not training in Tracing the Boilers, but working some topics of boiler tracing in order to bring the student to see and better understand some basic concepts of geometry inherent to high school instruction, since in this way he will have the opportunity of a practical activity. We begin by presenting a brief history of geometry, delineating how it has being developed and crafted for thousands of years, and how the evolution of mathematics developed by great characters influenced the development and growth of societies as well as humanity as a whole, and further, how geometry is still crafted in society in general. In this work we examine how and to what extent a more technical classroom professionalizing activity can assist the needs of the curriculum of high school and even more, wondering whether the high school curriculum meets the needs of the contemporary challenges of the 21st. century society, which is increasingly characterized by intensive use of knowledge, either to work, socialize or exercise citizenship. The research methodology used was the Didactical Engineering, that guided us in the creation and use of a planned teaching sequence, in a group of students, for the teaching and learning of geometric concepts, drawn from the observation of the difficulty faced by students to understand these concepts.
Keywords: Geometria; Traçados geométricos; Caldeiraria; Prática docente; Matemática - ensino; História da geometria; History of geometry; Teaching geometry in high school; Boiler; Geometric strokes; Planning; Geometry; CIENCIAS EXATAS E DA TERRA::MATEMATICA